2011
DOI: 10.1021/ja2086195
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Proof for an Extended Hydrogen-Bonding Network in Small Prolyl Isomerases

Abstract: Parvulins compose a family of small peptidyl-prolyl isomerases (PPIases) involved in protein folding and protein quality control. A number of amino acids in the catalytic cavity are highly conserved, but their precise role within the catalytic mechanism is unknown. The 0.8 Å crystal structure of the prolyl isomerase domain of parvulin Par14 shows the electron density of hydrogen atoms between the D74, H42, H123, and T118 side chains. This threonine residue has previously not been associated with catalysis, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 20 publications
2
70
0
Order By: Relevance
“…17 The results are consistent with the tautomers of the corresponding histidines identified in the high-resolution crystal structure of Par14, a PPIase homologous to Pin1. 16 Our NMR results showed that the hydrogen bond network exists as in the Par14 crystal structure; however, NMR could not directly observe the sample if C113 was in the thiolate or thiol form. 17 As described in the Results, the unusual 1 H− 15 N and 1 H− 13 C HSQC spectra for the imidazole rings in the mutants could represent chemical exchange between the different protonation states of the H59 imidazole ring ( Figure 9B,C).…”
Section: Biochemistrymentioning
confidence: 63%
See 4 more Smart Citations
“…17 The results are consistent with the tautomers of the corresponding histidines identified in the high-resolution crystal structure of Par14, a PPIase homologous to Pin1. 16 Our NMR results showed that the hydrogen bond network exists as in the Par14 crystal structure; however, NMR could not directly observe the sample if C113 was in the thiolate or thiol form. 17 As described in the Results, the unusual 1 H− 15 N and 1 H− 13 C HSQC spectra for the imidazole rings in the mutants could represent chemical exchange between the different protonation states of the H59 imidazole ring ( Figure 9B,C).…”
Section: Biochemistrymentioning
confidence: 63%
“…The histidines in the dual-histidine motif engage in the hydrogen bond network, in which H59 and H157 are in ε-and δ-tautomers, respectively. 16,17 In our previous work, we showed that impairing the hydrogen bond between H59 and H157 destabilized the structure. 17 The change in the protonation states of the histidines, which is theoretically predicted to occur according to the state of C113, 20 should have a significant impact on the structure and dynamics of these residues.…”
Section: Biochemistrymentioning
confidence: 94%
See 3 more Smart Citations